2009
DOI: 10.3844/ajas.2009.328.331
|View full text |Cite
|
Sign up to set email alerts
|

Refractive Index and Fourier Transform Infrared Spectra of Virgin Coconut Oil and Virgin Olive Oil

Abstract: : This study presents the refractive index and FTIR spectra of virgin coconut oil and virgin olive oil that have been measured in the wavelength range from 491.0-667.8 nm. The measurement of refractive index was carried out using a minimum deviation method while the IR transmission ranging from 600-4000 cm −1 was measured using FTIR spectrometer respectively. The measurements were done at room temperature and the dispersion equations for the studied samples were verified and the Cauchy constants were obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
1
3
0
3
Order By: Relevance
“…The above mentioned data revealed that no lipolysis and /or oxidative rancidity occurred in the oil under study. Therefore, the oil can be used in study and the previous obtained data were in harmony with the findings of(Firestone, 2005) ,Hilali et al, (2005) andYunus et al, 2009). Physicochemical properties of the Sunflower oil.…”
supporting
confidence: 81%
“…The above mentioned data revealed that no lipolysis and /or oxidative rancidity occurred in the oil under study. Therefore, the oil can be used in study and the previous obtained data were in harmony with the findings of(Firestone, 2005) ,Hilali et al, (2005) andYunus et al, 2009). Physicochemical properties of the Sunflower oil.…”
supporting
confidence: 81%
“…These hexane extracts mainly contained fats/oils and other non-polar constituents of the coconut water samples. The peak assignment of each peak and shoulder can be found in several literatures (Innawong et al, 2004;Kalsi, 2000;Lima et al, 2008;Vlachos et al, 2006;Yang & Irudayaraj, 2001;Yunus, Fen, & Yee, 2009) and the result is presented in Table 2.…”
Section: Effects Of Storage Duration (0 Days Storage Versus 21 Days Smentioning
confidence: 98%
“…Therefore, it was observed that the absorption peaks are the same for all the oil samples before and after five days of frying (Table 4). C-H stretching absorption occurs at a wavelength of 2922 cm peaks observed at methylene and methyl groups appear at 1458 and 1377 cm -1 [29,30,31].…”
Section: Functional Group Characterization Oil Before and After Fryingmentioning
confidence: 99%